University Living Labs: New Possibilities for Assistive Technologies and Sustainable Development; [Laboratorios Vivientes Universitarios: Nuevas Posibilidades Para Tecnologías Asistivas y el Desarrollo Sostenible] - Moreno-Munoz, C; Olguin-Vidal, J (Universidad del Zulia, 2023)
In recent years, universities have taken a leading role in innovation and technology transfer in communities. The objective of this article is a theoretical reflection on the figure of living laboratories as a tool to expand the possibilities of design, manufacture and distribution of assistive technologies in a sustainable way, through the review of recent literature on the topics raised. The results show that, from university industrial design workshops, spaces for dialogue between alternative assistive technologies, industry, entrepreneurship and the community can emerge, by enhancing four key elements of living labs: financing, values, communication and infrastructure. It is concluded that, considering living labs as the next evolutionary step of university workshops would enhance the development of assistive technologies in a sustainable environment. © 2023, Universidad del Zulia. All rights reserved.